Evaluating Usability, User Experience, and Playability of a Puzzle Game in Mixed Reality - Campos, Thiago Prado de; Hounsell, Marcelo da Silva; Damasceno, Eduardo Filgueiras; Valentim, Natasha M. C. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
This study investigates the usability, user experience (UX), and playability of a mixed reality (MR) game called Cubism, which allows participants to interact with holograms using hand gestures. We conducted an experiment with seven participants to evaluate their interaction with the game. The Usability and User Experience Evaluation in Touchable Hologram (UUXE-ToH) questionnaire was the primary data collection instrument to capture participants' perceptions of usability, satisfaction, and overall experience. Our findings indicate that the mixed reality environment of Cubism offers an engaging and intuitive user experience, though several challenges were identified. These insights contribute to the growing body of knowledge on human-computer interaction in mixed-reality contexts and suggest avenues for improving the design of future mixed-reality games. This research is valuable to the VR/AR/MR community by highlighting the critical factors influencing user interaction and satisfaction in MR games.